2019
DOI: 10.1002/smll.201804115
|View full text |Cite
|
Sign up to set email alerts
|

Unique 1D Cd1−xZnxS@O‐MoS2/NiOx Nanohybrids: Highly Efficient Visible‐Light‐Driven Photocatalytic Hydrogen Evolution via Integrated Structural Regulation

Abstract: Development of noble‐metal‐free photocatalysts for highly efficient sunlight‐driven water splitting is of great interest. Nevertheless, for the photocatalytic H2 evolution reaction (HER), the integrated regulation study on morphology, electronic band structures, and surface active sites of catalyst is still minimal up to now. Herein, well‐defined 1D Cd1−xZnxS@O‐MoS2/NiOx hybrid nanostructures with enhanced activity and stability for photocatalytic HER are prepared. Interestingly, the band alignments, exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 65 publications
(54 reference statements)
0
26
0
Order By: Relevance
“…In a heterogeneous PC system, hydrogen and oxygen can be collected simultaneously, presenting the advantage for practical industrial applications. With regard to the modulation of the PC water splitting by defect engineering, Wang et al reported 1D Cd 1− x Zn x S@O‐MoS 2 /NiO x hybrids by the integration of oxygen‐incorporated MoS 2 (O‐MoS 2 ) and NiO x with abundant defects that endowed a remarkable hydrogen evolution rate of 223.17 mmol h −1 g −1 in Na 2 S/Na 2 SO 3 solution as the sacrificial agent and an apparent quantum yield of 64.1% at 420 nm as well as outstanding durability (Figure a,b) . The heterostructures by the integration of WO 3 and V s ‐ZnIn 2 S 4 with NiS quantum dots reached the high PC hydrogen production rate of 11.09 mmol g −1 h −1 under visible‐light irradiation and an apparent quantum efficiency of 72% at 420 nm (Figure c,d) .…”
Section: Application Of Defect Engineering For Solar Energy Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a heterogeneous PC system, hydrogen and oxygen can be collected simultaneously, presenting the advantage for practical industrial applications. With regard to the modulation of the PC water splitting by defect engineering, Wang et al reported 1D Cd 1− x Zn x S@O‐MoS 2 /NiO x hybrids by the integration of oxygen‐incorporated MoS 2 (O‐MoS 2 ) and NiO x with abundant defects that endowed a remarkable hydrogen evolution rate of 223.17 mmol h −1 g −1 in Na 2 S/Na 2 SO 3 solution as the sacrificial agent and an apparent quantum yield of 64.1% at 420 nm as well as outstanding durability (Figure a,b) . The heterostructures by the integration of WO 3 and V s ‐ZnIn 2 S 4 with NiS quantum dots reached the high PC hydrogen production rate of 11.09 mmol g −1 h −1 under visible‐light irradiation and an apparent quantum efficiency of 72% at 420 nm (Figure c,d) .…”
Section: Application Of Defect Engineering For Solar Energy Conversionmentioning
confidence: 99%
“…a,b) Energy‐band alignments and schematic illustration of solar water splitting over Cd 1− x Zn x S@O‐MoS 2 /NiO x hybrids. Reproduced with permission . Copyright 2019, Wiley‐VCH.…”
Section: Application Of Defect Engineering For Solar Energy Conversionmentioning
confidence: 99%
“…The synthesis of 1D Cd 1−x Zn x S solid solutions was carried out according to the ethanediamine-assisted solvothermal method reported in our recent work [34].…”
Section: Synthesis Of One-dimensional (1d) CD 1−x Zn X S Solid Solutionsmentioning
confidence: 99%
“…1. Firstly, the 1D Cd 1−x Zn x S solid solutions with different aspect ratios were prepared by an ethylenediamine-directing solvothermal strategy [34]. Subsequently, the Cd 1−x Zn x S was ultrasonically dispersed in EG solution containing different concentrations of WCl 4 , which was then stirred for 30 min before it was rinsed with ethanol and water and dried in an oven to produce…”
Section: Electrochemical and Photoelectrochemical Measurementsmentioning
confidence: 99%
“…Nevertheless, there is still a series of adverse factors during the photocatalytic reaction process of Cd 1‐ x Zn x S, such as easy agglomeration of Cd 1‐ x Zn x S nanoparticles, the rapid recombination of the electron–hole pairs as well as the serious photocorrosion (i.e., S 2‐ in Cd 1‐ x Zn x S oxidized by photoinduced holes) . To deal with the above‐mentioned problems, various methods have been developed to enhance the photocatalytic activity and photochemical stability, including nano‐/microstructure control, metal or non‐metal elements doping and heterojunction construction, etc . However, the reported routine methods are incapable of solving all the disadvantages in Cd 1‐ x Zn x S in one pot, particularly the photocorrosion.…”
Section: Introductionmentioning
confidence: 99%